Investigation of Adolescent Pregnancy Outcomes and Postpartum Depression Frequency and Risk Factors: Prospective Case Control Study - Budak, Mehmet Sukru; Akgol, Sedat (Gynecology Obstetrics & Reproductive Medicine, 2020)
Objective: The aim of this study was to evaluate the frequency of postpartum depression (PPD), accompanying risk factors, and obstetrics and neonatal outcomes in adolescent pregnancies. Study Design: This prospective study was conducted on adolescent and adult pregnant patients giving birth in Diyarbakır Gazi Yaşargil Training and Research Hospital of Health Sciences University between January 01 and 31, 2018. Groups were compared in terms of PPD rates and PPD-related factors were also determined in both groups. Results: The frequency of PPD was higher in adolescent patients than in adult patients but the difference was not considered statistically significant (p> 0.05). In adolescent and adult patients, the following factors were found to increase PPD risk: illiteracy, living in an urban area, divorced parents, having fewer than 4 siblings, anemia and caesarean delivery. Conclusion: The study results showed no significant difference in PPD rates between adolescent and adult pregnant patients. In both groups, the factors of illiteracy, living in an urban area, divorced parents, anemia, fewer than 4 siblings, and caesarean delivery were found to increase the risk of development of PPD.